Relevance of the Position of the Victims in Indonesian Positive Law and Islamic Criminal Law - Yayan Muhammad Royani (Universitas Islam Negeri Walisongo Semarang, 2022)
The position of the victim in the criminal justice system is not considered as a subject or object. These problems are inseparable from the understanding that criminal law only regulates the relationship between the state and individuals. Positive laws governing the position of victims are contained in the Criminal Code and Criminal Procedure Code as well as regulations outside the criminal justice system. The regulation is very limited to the victim as a legal object, not a determinant. In the perspective of Islamic law, the position of the victim is regulated in the crime of qisas and takzir. Victims get the right to determine punishment for criminals by implementing qisas, forgiveness or diyat. In the takzir crime, the ruler or judge can determine to compensate the victim as a forgiving or reducing crime. This research is a normative juridical research with a comparative approach. The results of the study indicate that there are similarities and differences in the regulation regarding the position of victims in positive law and Islamic law. Equality lies in the types of rights received by victims in the form of material compensation, compensation, restitution and rehabilitation except in takzir in the form of a decision to marry a rape victim. The difference lies in the position of the victim in positive law which does not include the victim as part of the criminal justice system, while in Islamic law as in qisas, the victim is an inseparable part of the criminal justice system.Kedudukan korban dalam sistem peradilan pidana tidak dianggap sebagai subjek ataupun objek. Permasalahan tersebut tidak terlepas dari pemahaman bahwa hukum pidana hanya mengatur hubungan antara negara dan individu. Hukum positif yang mengatur tentang kedudukan korban terdapat dalam KUHP dan KUHAP serta regulasi di luar sistem peradilan pidana. Pengaturannya sangat terbatas kepada korban sebagai objek hukum bukan penentu. Dalam perspektif hukum Islam kedudukan korban diatur dalam tindak pidana qisas dan takzir. Korban mendapatkan hak sebagai penentu hukuman bagi pelaku tindak pidana dengan pelaksanaan qisas, pemaafan atau diyat. Pada tindak pidana takzir penguasa atau hakim dapat menentukan mengganti kerugian korban sebagai pemaaf atau pengurang tindak pidana. Penelitian merupakan penelitian yuridis normatif dengan pendekatan perbandingan. Hasil penelitian menunjukkan bahwa terdapat persamaan dan perbedaan pengaturan tentang kedudukan korban dalam hukum positif maupun hukum Islam. Persamaan terletak pada jenis hak yang diterima korban berupa pengganti kerugian materi, konpensasi, restitusi dan rehabilitasi kecuali dalam takzir berupa putusan untuk menikahi seorang korban perkosaan. Perbedaan terletak pada kedudukan korban dalam hukum positif yang tidak memasukan korban bagian dalam sistem peradilan pidana, sedangkan dalam hukum Islam sebagaimana qisas, korban merupakan bagian yang tidak terpisahkan dari sistem peradilan pidana